Fresno County Board of Supervisors' Installation Ceremony - Watkins, Howard::::::::: (1981)
Bruce Bronzan holding Chloe Bronzan, Mary Bronzan, Peggy Bronzan, Nick Bronzan and audience watching McClane High Color Guard dance